FEATURES OF SEXUAL DIMORPHISM IN ELITE PENTATHLETES - Asienkiewicz, R.; Sevdalev, S.V.; Vrublevskiy, E.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to establish the degree of manifestation of sexual dimorphism in elite athletes specializing in modern pentathlon. Methods and structure of the study. The study involved 18 elite athletes, both men and women, specializing in modern pentathlon and having the sports qualifications from MS to WCMS. In order to address the research issues, somatometric methods commonly used in sports morphology were applied. In addition, the method of bioimpedance analysis of body composition using the "Medass – ABC-01" device (Russia) was applied. Conclusion. The study found that, according to the morphological characteristics, the degree of manifestation of sexual dimorphism in elite pentathletes was low to average. The body composition analysis revealed the high (SMM, IW and TBW, ACM), average (EW, fat mass) and low (percent SMM) degrees of manifestation of sexual dimorphism. In terms of almost all the studied indicators, the men were found to predominate over women, except for the fat mass. To reduce the degree of manifestation of sexual dimorphism, attention should be paid to the sports selection of female athletes.